IMPLEMENTASI UNDANG- UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DALAM UPAYA MELINDUNGI KEPENTINGAN ANAK - Varida Ariani, Nevey (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
ChildrenÂ areÂ a mandateÂ from God Almighty whichÂ inÂ themÂ laidÂ aÂ dignityÂ as humanÂ beings.Â ChildrenÂ need protection against negative effects of a fast-growing developmnet. This essay is trying to discuss about howâs theÂ implementation ofÂ theÂ lawÂ ofÂ SPPAÂ andÂ theÂ Government ofÂ IndonesiaâsÂ effortsÂ in protectingÂ children especially those who are conflicted with the law in accordance to The Law number 11 Year 2012. The method applied in this essay is qualitative socio-legal approach, based on theÂ library data. In the investigation process, prosecutionÂ untilÂ theÂ proceedings,Â thereÂ stillÂ be diversionÂ processÂ IsÂ ultimatelyÂ enforcedÂ consideringÂ the childrenâs age and the penalties are not over than 7 years.Â If this diversion processÂ is not applicableÂ then the judicial process is becoming ultimum remedium, putting the children in LPAS, LPAK and LPKS. Those institutions areÂ expectedÂ to giveÂ new hopesÂ toÂ children whoâs dealing withÂ theÂ legal matters.Â ThroughÂ theÂ approching systemÂ inÂ JuvenileÂ CriminalÂ CourtÂ ProcessÂ fromÂ investigators, prosecutors,Â judges,Â advocatesÂ toÂ theÂ public counselor, bothÂ the Ministry ofÂ LawÂ and Human Rights andÂ theÂ Social Ministry,Â itÂ isÂ necessaryÂ to establishÂ a clearÂ coordinationÂ andÂ roleÂ inÂ implementingÂ theÂ Juvenile Criminal CourtÂ System.